The effect of salt and temperature on the conformational changes of P1LEA‐22, a repeat unit of plant Late Embryogenesis Abundant proteins. (11th March 2020) - Léon, David; Vermeuel, Michael P.; Gupta, Priya; Bunagan, Michelle R.
Abstract : The effect of choline chloride on the conformational dynamics of the 11‐mer repeat unit P1LEA‐22 of group 3 Late Embryogenesis Abundant (G3LEA) proteins was studied. Circular dichroism data of aqueous solutions of P1LEA‐22 revealed that the peptide favors a polyproline II (PPII) helix structure at low temperature, with increasing temperature promoting a gain of unstructured conformations. Furthermore, increases in sample FeCl3 or choline chloride concentrations causes a gain in PPII helical structure at low temperature. The potential role of PPII structure in intrinsically disordered and G3LEA proteins is discussed, including its ability to easily access other secondary structural conformations such as α‐helix and β‐sheet, which have been observed for dehydrated G3LEA proteins. The observed effect of FeCl3 and choline chloride salts on P1LEA‐22 suggests favorable cation interactions with the PPII helix, supporting ion sequestration as a G3LEA protein function. As choline chloride is suggested to improve salt tolerance and protect cell membrane in plants at low temperature, our results support adoption of the PPII structure as a possible damage‐preventing measure of Late Embryogenesis Abundant proteins. Abstract : Circular dichroism data of aqueous P1LEA‐22, the 11‐mer repeat unit of group 3 Late Embryogenesis Abundant (G3LEA) proteins, revealed that the peptide accesses polyproline II (PPII) helix structure at low temperature, the signal of which can be enhanced by the presence of FeCl3 or choline chloride. The potential role of PPII structure in intrinsically disordered proteins is discussed, including its ability to access other secondary structural conformations such as α‐helix and β‐sheet, which have been observed for dehydrated G3LEA proteins.